2015
DOI: 10.1186/s12888-015-0484-z
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers to recruiting ethnic minorities to mental health research: a typology of recruitment strategies

Abstract: BackgroundThe ethnic minority population in developed countries is increasing over time. These groups are at higher risk of mental illness and demonstrate lower participation in research. Published evidence suggests that multiple factors like stigma, lack of trust, differences in explanatory models, logistical issues and lack of culturally aware researchers act as barriers to ethnic minority recruitment into mental health research. To reduce inequalities in participation, there is a need to devise innovative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 28 publications
3
95
0
Order By: Relevance
“…Five out of six of the SRs (SR1, SR2, SR3, SR4, SR6) reported improvements in participant physical health or self-care management skills, while only three SRs (SR1, SR5, SR6) reported improvement in a few psychosocial and mental health outcomes. This is in accordance with the challenges associated with recruiting minority populations for clinical trials or for mental health research, as found by Mason et al (2003) as well as Waheed et al (2015). Our analysis suggests that there is evidence supporting the effectiveness of web-based interventions improving ethnic minority and historically underserved community's health, ranging from weight management, asthma and diabetes knowledge and medical adherence.…”
Section: Ehealth and Mhealth Technology Usesupporting
confidence: 86%
“…Five out of six of the SRs (SR1, SR2, SR3, SR4, SR6) reported improvements in participant physical health or self-care management skills, while only three SRs (SR1, SR5, SR6) reported improvement in a few psychosocial and mental health outcomes. This is in accordance with the challenges associated with recruiting minority populations for clinical trials or for mental health research, as found by Mason et al (2003) as well as Waheed et al (2015). Our analysis suggests that there is evidence supporting the effectiveness of web-based interventions improving ethnic minority and historically underserved community's health, ranging from weight management, asthma and diabetes knowledge and medical adherence.…”
Section: Ehealth and Mhealth Technology Usesupporting
confidence: 86%
“…In most of the studies, implementers provided the required devices to any participants who lacked access to allow for study participation but that just begs the question. Access is improving, but individuals living in low SES neighborhoods still experiences lower rates of Internet connectivity (Fairlie 2005; Waheed et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Ferguson (2002) argued that since both family and disability are culturally constructed, the ways in which mothers and fathers from differing cultural backgrounds experience and make sense of disability will vary considerably. Waheed et al (2015) identified 33 barriers to recruiting participants from ethnic minority groups to mental health research studies which they categorised in relation to five themes, namely: participant related barriers; practical issues; family/community related; health service related and research process related. They subsequently developed a typology of recruitment strategies aimed at overcoming these specific barriers, including for example, the planning of outreach activities in target communities and engaging the services of a "culturally competent" insider to facilitate access.…”
Section: Discussionmentioning
confidence: 99%